Validity and reliability of the Chinese version of the Young Positive Schema Questionnaire - Chi, Danni; Du, Xiangju; Ma, Hong; Wang, Yubo; Zhang, Yuanyuan; Zhong, Haiyun (Frontiers in Psychology, 2022)
Young Positive Schema Questionnaire (YPSQ) examines early adaptive or positive schemas as a counterpart to early maladaptive ones. This study investigated the validity and reliability of the Chinese version of the YPSQ (CYPSQ). A convenient community sample of 634 individuals, most of whom were college students, were recruited through a mobile survey. R Careless was used to screen for careless responses. A final sample of 336 was obtained. Confirmatory factor analyses of the CYPSQ were examined using SPSS AMOS 25. Other statistical analyses were conducted using SPSS 25. An 11-factor CYPSQ was identified with an acceptable factors structure (2/df = 2.13, SRMR = .04, RMSEA = .06, GFI = .80, TLI = .90, and CFI = .91). Convergent and discriminant validity were confirmed in most aspects. Concurrent validity was evident with resilience, life satisfaction, depression, and anxiety. Internal reliability was satisfied as the Cronbach’s alphas of the 11 factors of the CYPSQ ranged between .70 and .88. The findings supported the reliability and validity of the CYPSQ in Mainland China.